2018
DOI: 10.1186/s13058-018-1054-3
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-derived granulocyte colony-stimulating factor diminishes efficacy of breast tumor cell vaccines

Abstract: BackgroundAlthough metastasis is ultimately responsible for about 90% of breast cancer mortality, the vast majority of breast-cancer-related deaths are due to progressive recurrences from non-metastatic disease. Current adjuvant therapies are unable to prevent progressive recurrences for a significant fraction of patients with breast cancer. Autologous tumor cell vaccines (ATCVs) are a safe and potentially useful strategy to prevent breast cancer recurrence, in a personalized and patient-specific manner, follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 80 publications
(57 reference statements)
3
23
0
Order By: Relevance
“…It is conceivable that such tumor-derived signals are able to program myeloid cells towards an tumor-promoting phenotype, with systemic effects targeting spleen and bone marrow. A crucial factor involved in the generation and pathological activation of PMN-MDSC is the growth factor G-CSF, and systemic levels of G-CSF have been correlated with MDSC accumulation in several tumor models [46, 51, 52]. We speculate that G-CSF also accounts for the pathological activation of PMN-MDSC in KPC-derived pancreatic cancer, as elevated G-CSF serum levels during tumor progression correlated with the frequency of PMN-MDSC in spleen and blood.…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that such tumor-derived signals are able to program myeloid cells towards an tumor-promoting phenotype, with systemic effects targeting spleen and bone marrow. A crucial factor involved in the generation and pathological activation of PMN-MDSC is the growth factor G-CSF, and systemic levels of G-CSF have been correlated with MDSC accumulation in several tumor models [46, 51, 52]. We speculate that G-CSF also accounts for the pathological activation of PMN-MDSC in KPC-derived pancreatic cancer, as elevated G-CSF serum levels during tumor progression correlated with the frequency of PMN-MDSC in spleen and blood.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are essentially in agreement with several earlier experimental studies in murine models of experimental colon cancer and NSCLC, in which neutrophilic inflammation resulting from tumor expression of the neutrophil-recruiting cytokine IL-17A was associated with disease progression and decreased responsiveness to PD-1-targeted immunotherapy [39,40]. In a somewhat similar context, another recent experimental animal study revealed that production of G-CSF by murine breast carcinomas was associated with attenuation of the therapeutic activity of breast tumor-targeted vaccines [41].…”
Section: Recruitment and Exploitation Of Neutrophils By Tumorsmentioning
confidence: 57%
“…To examine whether MPLAs provokes the production of immunosuppressive cytokines, we collected the conditioned media from MPLAs-treated A375 cells and conducted a cytokine array assay. Results showed that several immunosuppressive cytokines, including ICAM-1 21 , IL-6 22 , CXCL12 22 , G-CSF 23 , and PAI-1 24 , were increased upon MPLAs stimulation (Fig. 3e, f).…”
Section: Tlr4 Ligands Promote Stat3-mediated Cellular Events In Melanmentioning
confidence: 92%